Decision-making under risk and theory of mind in adolescent offenders in provisional deprivation of liberty - Loureiro,Rubens José (2022)
Abstract Introduction Delinquent behaviors are risky behaviors that increase during puberty and reach their highest peak in late adolescence. It has been proposed that poor decision-making and theory of mind (ToM) are key cognitive processes implicated with delinquency during adolescence, affecting evaluation of risks and impairing appreciation of social norms. Nevertheless, it is not yet clear whether adolescent offenders who are subjected to provisional deprivation of liberty due to conflict with the law (adolescents in conflict with the law [ACL]) might, in fact, present a specific profile with regard to these cognitive processes. Objectives To assess deliberative decision-making and ToM among adolescents in conflict with the law and adolescents not in conflict with the law. Methods The sample comprised 62 participants: ACL (n = 29) and a control group (CG) (n = 33). ToM was assessed with the Reading the Mind in the Eyes Test (RMET) and decision-making was assessed with the Columbia Card Task (CCT). Substance use, callous-unemotional traits, childhood maltreatment, and intelligence quotient (IQ) were also assessed. Results ACL had more ToM errors for negative mental states in comparison to CG, but not for error rates concerning neutral and positive mental states. With regards to decision-making, our results suggest that ACL group members did not vary their behavior based on the available information and that the risk information had an opposite effect on the number of cards chosen (risk-taking behavior) when compared to CG. Conclusion These findings have important implications for development of interventions for these adolescents, suggesting that they tend to learn little from negative outcomes and have reduced capacity to process negative emotions.